Perancangan sistem transmisi penggerak mesin bubut mini konvensional - Muhammad Luqman; Agung Dwi Sapto (Jurnal Teknik Mesin Indonesia, 2023)
Lathe is one of the metal cutting machines with the main motion spinning, where the workpiece is gripped and rotated on its axis, while the cutting tool moves to cut along the workpiece. In the design of conventional mini lathes there are main parts that are fixed heads and drive power units, this lathe can be used for all circles because it uses materials or components that are easy to obtain. In the design of a product is made first the design of the tool and continued by doing calculations on the design of this tool is in the form of a shaft that is also connected to a fixed head, peg, pulley, v belt, bearing, drive motor and engine frame as a mount of the components above. The results of the design of the transmission system driving this lathe indicate that the stress on the transmission shaft is still below the allowable stress, so that the lathe is safe to use.